New insights on the shell-crusher shark Ptychodus decurrens Agassiz, 1838 (Elasmobranchii, Ptychodontidae) based on the first known articulated dentition from the Upper Cretaceous of Croatia - Manuel Amadori; Sanja Japundžić; Jacopo Amalfitano; Luca Giusberti; Eliana Fornaciari; Patrick L. Jambura; Jürgen Kriwet (Swiss Journal of Palaeontology)
Abstract A new lower tooth plate of Ptychodus decurrens from the Turonian (Upper Cretaceous) of the Dalmatian region (southern Croatia) is documented here for the first time. The specimen represents the first articulated dentition of a ptychodontid shark that has been discovered from the Balkan Peninsula and the most complete ever found for the un-cuspidate species P. decurrens up to now. The reconstruction of the entire lower dentition of P. decurrens based on this exceptionally well-preserved dentition shows a wider crushing plate than previously hypothesised with bulgy teeth limited to the central area. Even though a defined cusp is missing, the occlusal surface of the teeth is undeniably raised and bulgy in some un-cuspidate species of Ptychodus (e.g., P. decurrens). This compels us to reconsider the use of terms such as high- and low-crowned as well as cuspidate and un-cuspidate. In addition, specimens previously assigned to dubious species (P. depressus, P. levis and P. oweni) or even varieties (P. polygyrus var. sulcatus and P. decurrens var. multiplicatus) are reassigned here to P. decurrens based on a careful comparison of the type materials. The reassessment of tooth root morphologies provides indicative traits for the identification of different genera of ptychodontid sharks (Paraptychodus and Ptychodus). The taxonomic revision presented here is crucial for securing a stable taxonomy and systematics of the shell-crushing shark P. decurrens, as well as of all ptychodontid sharks. The resulting updated taxonomy, together with the description and reconstruction of the new crushing plate, greatly contribute to a better understanding of one of the most enigmatic families (Ptychodontidae) of Mesozoic elasmobranchs. The detailed investigation of the new dentition of Ptychodus from Dalmatia is also a further step towards the discovery of Upper Cretaceous ichthyofaunas of one of the most palaeontologically important areas of the Balkan Peninsula.